Ultrastructural alterations in mouse capillary blood vessels after experimental injection of venom from the snake Bothrops asper (Terciopelo) - Moreira Carmona, Lisela (1992)
Histological and ultrastructural alterations in capillary blood vessels were studied at various time intervals after im injection of 50 micrograms of Bothrops asper snake venom in mouse gastrocnemius muscle. Hemorrhage was observed as early as 5 min after envenomation, as abundant erythrocytes appeared in the interstitial space. Ultrastructural observations revealed two different patterns of pathological changes: in the majority of damaged capillaries, endothelial cells had blebs and cytoplasmic projections pinching off to the lumen. This phenomenon was observed together with a decrease in the number of pinocytotic vesicles, with endothelial cells becoming very thin. As an apparent consequence of this process, some endothelial cells had evident gaps in their continuity. In addition, basal laminae surrounding these capillaries were altered and discontinuous. Other endothelial cells underwent a morphologically different process of degeneration, characterized by swelling of the endoplasmic reticulum and of the cytosol. These cells had a diffuse appearance and their basal laminae were discontinuous or absent. No major changes in the intercellular junctions were noticed in damaged endothelial cells. Samples obtained 30 and 60 min after venom injection were devoid of normal capillaries in many areas, and only diffuse remnants of their structure were found. Many altered capillaries had platelet aggregates and fibrin, the latter also being observed in the interstitial space. It is concluded that B. asper venom induces rapid and drastic pathological effects on capillaries leading to hemorrhage per rhexis i.e., erythrocytes probably escape through gaps in damaged endothelial cells and not through widened intercellular junctions.